Factors influencing the working efficiency of women engaged in stone breaking with special reference to nutritional status - Jyothi Augustine (Department of Home Science, College of Agriculture, 1993)
A study on the factors influencing the working efficiency of women engaged in stone breaking with special reference to the nutritional status was taken forth to evaluate the socio – economic and food consumption pattern of the families, personal characteristics, working pattern energy balance and nutritional status of the respondents.